KATEKIS SEBAGAI KONSELOR DALAM PENGEMBANGAN IMAN - Lumbanbatu, Johannes; Sihotang, Din Oloan; Ginting, Elisa (STP St. Bonaventura Medan, 2021)
Catechists are individuals chosen by the Church to introduce Christ to those who do not know Him, especially the youth. Their role is crucial in the Church's evangelization efforts, addressing changing challenges with creativity. As counselors, they assist and accompany young people in finding solutions to their problems. The youth require support from the Church, society, and family for their spiritual development. Crisis of faith often stems from their lack of understanding of their responsibilities. The youth are a vital force in both the Church and society, and the role of catechists as counselors is pivotal in their faith development